Prosodic reading and reading comprehension in university - Aulia Rahmawati; Ida Rosmalina; Hesti Wahyuni Anggraini (Universitas Islam Sultan Agung, 2020)
This study was aimed at investigating the students’ English reading comprehension on the basis of the importance of prosodic reading in university level by first, measuring the levels of reading prosody and reading comprehension, characterizing the acoustic characteristics produced by the students, and at last associating the first variable to the second variable. Prosodic reading levels were measured by using Multidimensional Fluency Scale, containing four dimensions. To explore the six types of syntactically complex structures produced by the students orally, this study conducted a descriptive analysis, only focused on some features. The findings showed that the students experienced moderate level of reading prosody and reading comprehension. Also, it could be reported that a significant correlation was found between the two variables. The study reported that prosodic reading contributed to reading comprehension with r-obtained .538. A thorough analysis explained that some other related predictors influenced students’ comprehension, like difficulties in recognizing the vocabulary, lack of knowledge to review the four types of sentences, and the length of the passage. Among four dimensions, only pace and expression & volume did contribute to reading comprehension much. Different pause structures produced by the students and the native speakers were clearly identified. This was shown as many students had a long pause and sound hesitate due to their inability to decode the words. Moreover, most of them could not comprehend the sentence structure of the text, when to pause, which words were needed to be stressed, and the intonation used. As a result, they read in a two-three phrases and declined to notice where the endings of sentences and clauses were definitely stated. These results confirmed that pause structure commits as a pivotal factor in determining students’ reading comprehension.